A Double-Boost Converter Based on Coupled Inductance and Magnetic Integration - Hongzhu Li; Ling Zhu; Le Wang (Active and Passive Electronic Components)
High-voltage gain converter has a high-frequency use in some industrial fields, for instance, the fuel cell system, the photovoltaic system, electric vehicles, and the high-intensity discharge lamp. In order to solve the problem of the low-voltage gain of traditional boost converter, the double-boost converter with coupled inductance and doubled voltage is proposed, which connects the traditional boost converter in parallel. The voltage gain of the converter is further improved by introducing the voltage-doubled unit of the coupled inductance. Moreover, the clamp capacitor can absorb the leakage inductance in the circuit and reduce the voltage stress of the switch. In addition, two coupled inductors are magnetically collected; then, the loss of the core is analyzed under the same gain. The detailed analysis of the proposed converter and a comparison considering other topologies previously published in the literature are also presented in this article. In order to verify the proposed converter performance, a prototype has been built for a power of 200 W, input and output voltages of 12 and 84 V, respectively, and a switching frequency of 50 kHz. Experimental results validate the effectiveness of the theoretical analysis proving the satisfactory converter performance, whose peak efficiency is 95.5%.